Split the Difference Beijing Modern Dance Company - Roy, Sanjoy (Dance Books Ltd., Alton,Hampshire (UK), 2008)
PALABRAS CLAVE: Chinese culture, Oath, Gao Yanjinzi, Unfettered Journey, Hu Lei's, Beijing Modern Dance Company.